2021
DOI: 10.3390/foods11010053
|View full text |Cite
|
Sign up to set email alerts
|

Generation Z Young People’s Perception of Sexist Female Stereotypes about the Product Advertising in the Food Industry: Influence on Their Purchase Intention

Abstract: Previous studies have generated important insights into consumer behavior. However, no study has addressed how to persuade young people belonging to Generation Z to increase the purchase intention of food products from a gender perspective. Drawing on ambivalent sexism theory, this paper explores the influence of the attitude toward advertising and the ethical judgment to predict consumers’ food product purchase intention. We applied a quantitative method, partial least squares structural equation modeling, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
20

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 76 publications
(95 reference statements)
0
7
0
20
Order By: Relevance
“…Notably, only two articles incorporated feminist theory into their analyses, as evidenced by the works of Kitsa and Mudra (2020) and Mager and Helgeson (2011). In addition, the trend attitudes related to the brand was studied using 10 different theories, with reactance theory ( n = 2; Åkestam et al, 2017; Åkestam et al, 2021), and ambivalent theory ( n = 2; Bermúdez‐González et al, 2022; Teng et al, 2021) being the most frequently employed. Furthermore, the trend of the sexualization of women in advertising was explored with only 4 theories, including cultivation theory (Rosewarne, 2005), feminist theory (Rudloff, 2020), limits of social responsibility (Alam et al, 2019), and the theory of objectification (Alam et al, 2019).…”
Section: Findings Discussion and Direction For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, only two articles incorporated feminist theory into their analyses, as evidenced by the works of Kitsa and Mudra (2020) and Mager and Helgeson (2011). In addition, the trend attitudes related to the brand was studied using 10 different theories, with reactance theory ( n = 2; Åkestam et al, 2017; Åkestam et al, 2021), and ambivalent theory ( n = 2; Bermúdez‐González et al, 2022; Teng et al, 2021) being the most frequently employed. Furthermore, the trend of the sexualization of women in advertising was explored with only 4 theories, including cultivation theory (Rosewarne, 2005), feminist theory (Rudloff, 2020), limits of social responsibility (Alam et al, 2019), and the theory of objectification (Alam et al, 2019).…”
Section: Findings Discussion and Direction For Future Researchmentioning
confidence: 99%
“…Mudra (2020) andMager and Helgeson (2011). In addition, the trend attitudes related to the brand was studied using 10 different theories, with reactance theory (n = 2;Åkestam et al, 2017; Åkestam et al, 2021), and ambivalent theory (n = 2;Bermúdez-González et al, 2022; Teng et al, 2021) being the most frequently employed.Furthermore, the trend of the sexualization of women in advertising was explored with only 4 theories, including cultivation theory(Rosewarne, 2005), feminist theory(Rudloff, 2020), limits of social responsibility(Alam et al, 2019), and the theory of objectification(Alam et al, 2019). Finally, the analysis of the trend of female empowerment in advertising encompassed insights from 16 different theories, with critical race theory(Sobande, 2019a;Sobande, 2019b), feminist theory(Karlsson & Ramasar, 2020;Sobande, 2019a), and social role theory(Olsen, 2022;Varghese & Kumar, 2022) emerging as the most recurrent theories adopted in this context.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we should not assume a total absence of perceived risk from endorsements, despite the commitment of audiences characterized by a high degree of involvement with their opinion referents, 15,17 as well as a strong desire for social interaction and co-creation of consumer experiences—characteristics shown by Gen Z. 45,49 This is particularly the case if we take into account the fact that SMI followers are becoming increasingly cognizant of the benefits that influencers receive through making recommendations. 23,88 There is also growing awareness of the regulatory limitations linked to the proliferation of influencer marketing, especially regarding recommendations that could affect people’s health.…”
Section: Literature Review: Hypothesis Development and Conceptual Modelmentioning
confidence: 99%
“…44 Most authors agree that the centennial generation is composed of those born in the mid- or late-90s. 3,28,4449 Although it is difficult to trace the thin line that separates one generation from another (for example, millennials and Gen Z), 44 these studies have revealed a series of identity characteristics of Gen Z: (a) they attach great importance to the information shared on social networks 28 ; (b) they devote time and effort to the online shopping process 46 ; (c) they justify their purchases as intelligent, based on the opinions of their peers in networks, and they consider interpersonal communication about the product to be very relevant 49 ; (d) they have a strong desire for social interaction, participation, and co-creation of consumer experiences 45 ; (e) they use communication technologies to search for product information, and they are continuously on social networks 47 ; (f) they are oriented toward fashion and product customization 3 ; and (g) they are less loyal as customers than representatives of previous generations. 47…”
Section: Introductionmentioning
confidence: 99%